Review of the genus Papagona Ball, 1935 (Hemiptera: Caliscelidae) including a new Neotropical species - de Freitas, Abner S.; Zahniser, James N.; Takiya, Daniela M. (Zootaxa, 2021)
Papagona Ball, 1935 was originally described based on two species from the USA (Arizona). Both species of Papagona (P. papoosa Ball, 1935, type species of genus, and P. succinea Ball, 1935) are redescribed herein based on type specimens, including their previously unknown internal male genitalia. A new species from Brazil (Roraima) is described herein including the male and female terminalia. A taxonomic key to all included species is provided and additional diagnostic characters for this genus are proposed.